Students' Perceptions of Learning in an Online Multiround Business Simulation Game: What Can We Learn from Them?. (12th November 2019) - Brazhkin, Vitaly; Zimmerman, Honey
ABSTRACT: Multiround business simulation games have been gaining popularity in higher education. However, certain aspects of experiential learning of individual students in the game remain unaddressed in research literature. Team assessments, such as team papers, appear a common, "natural" choice given the team‐based nature of the games but may potentially mask individual learning outcomes. In this study we use a qualitative method to glean from individual students' papers a deeper understanding of the process of learning of individual students in a team‐based, multiround business simulation game. Our findings indicate that individual and timely assessments are necessary to identify cases of not meeting the expected individual learning outcomes for the instructor's corrective intervention. This study contributes to the understanding of the process and outcomes of student learning in a multiround business simulation game, methods of teaching a supply chain and operations class with a simulation, and methods for better aligning course goals and assessments.